Implementation of Experiential Learning Learning Model Toward Students’ Science Generic Skills - Intania Dwi Melani; Wiwin Puspita Hadi; Eva Ari Wahyuni; Mochammad Ahied; Mochammad Yasir (Indonesian Journal of Mathematics and Natural Science Education, 2022)
his study aims to determine the generic science skills of students before and after learning using the Experiential Learning learning model. The research method in this study used a pre-experiment in the form of One Group Pretest and Posttest Design. The research instrument used was using a generic science test, student response questionnaires and observation sheets using the purposive sampling technique. The data analysis technique used paired sample t test. Based on the results of the study, it was found that (1) the Experiential Learning Model had an influence in training students generic science skills as evidenced by the significance obtained, namely 0.000 <0.05, (2) The average learning implementation of the Experiential The learning model was 100% with a very good category,Based on the results of this study, it can be concluded that the Experiential learning model has an influence on students' generic science skills so that the learning process is important to implement in other materials.